Exploring Student Perceptions and Experiences of Nearpod: A Qualitative Study - Paulina Erawati Paramita (Departement of Mathematics Education, 2023)
This qualitative study delves into student perceptions and experiences with Nearpod, a web-based educational platform, with a specific focus on understanding its impact on modern education. Thematic analysis of data collected from twenty students provides valuable insights into the platform's effectiveness. The findings reveal that Nearpod plays a crucial role in enhancing student engagement and attentiveness. The interactive nature of Nearpod, including features such as interactive presentations, quizzes, and real-time collaboration tools, significantly contributes to increased student participation. This thematic analysis underscores the platform's potential to create a more engaging and participatory learning environment.Additionally, the study highlights the positive impact of Nearpod's visual aids, simulations, and virtual reality components on student comprehension, making complex concepts more accessible. However, the research also identifies technical glitches and platform stability issues that need attention to ensure a seamless and uninterrupted learning experience.Furthermore, the thematic analysis suggests that greater customization options and a wider array of diverse interactive activities could cater to individual learning preferences, thereby further enhancing student engagement. Despite the study's limitations, such as a small sample size and a focus solely on student perspectives, the thematic analysis underscores Nearpod's potential as a valuable educational tool. It emphasizes the need for ongoing refinement to maximize its effectiveness in the ever-evolving educational landscape. In conclusion, this research highlights the significance of Nearpod in the digitized era of learning and its potential to transform modern education.